Building an integrated serosurveillance platform to inform public health interventions: Insights from an experts’ meeting on serum biomarkers - Kirsten E. Wiens; Barbara Jauregui; Benjamin F. Arnold; Kathryn Banke; Djibril Wade; Kyla Hayford; Adriana Costero-Saint Denis; Robert H. Hall; Henrik Salje; Isabel Rodriguez-Barraquer; Andrew S. Azman; Guy Vernet; et al. (PLoS Neglected Tropical Diseases, 2022)
Author summary The use of biomarkers to measure immune responses in serum is crucial for understanding population-level exposure and susceptibility to human pathogens. Advances in sample collection, multiplex testing, and computational modeling are transforming serosurveillance into a powerful tool for public health program design and response to infectious threats. In July 2018, 70 scientists from 16 countries met to perform a landscape analysis of approaches that support an integrated serosurveillance platform, including the consideration of issues for successful implementation. Here, we summarize the group’s insights and proposed roadmap for implementation, including objectives, technical requirements, ethical issues, logistical considerations, and monitoring and evaluation.